Clinical, endometrial histology and colpocytology with sequential therapy - Ludmir, A. (2015)
Clinical and histological evaluation was made in 109 patients under a mestranol-chlormadinone  combination for 2-3 cycles. 42 were private patients (62 cycles) and 67 were hospital patients (198 cycles). There were no clinical or other differences between the two groups. 1.5 % of the patients presented headache and nervous tension and 1.15 % had nausea as the only gastrointestinal complaint. Cycle duration was 26-30 days with no alteration in the length of menstruation although 5% of the cases had hypomenorrhea  B.B.T. curves were 100% monophasic. The endometrial biopsies taken the day following suspension of the tablets were 93.75 % of inicial secretory type and 6.25 % of late proliferative type. Colpo cytology from last day of medication or the day following suspension was compatible with days 16-24 of the normal cycle in 63.89 % of the cases and with days 10-14 in 36.11 % of them. From these preliminary evaluation we conclude that the combination used in sequential fashion, provokes minimal alterations, mimics closely normal cycles and acts as a very effective contraceptive.